Taponamiento cardiaco en dengue severo: Un reporte de caso - Laura Baquero-Tabares (Infectio, 2024)
Dengue infection is characterized by a wide spectrum of clinical manifestations. Cardiac involvement may include arrhythmias, myocarditis, or pericardial effusion, which in some cases may be asymptomatic, but can also be fatal. We describe the case of a 45-year-old woman with severe dengue infection. She presented with hypotension refractory to fluid therapy requiring vasopressor support without improvement in vital signs. Decreased voltage on electrocardiographic tracing, enlarge cardiac silhouette in chest radiograph, and point-of-care ultrasound confirmed the presence of cardiac tamponade. Ultrasound-guided pericardiocentesis was performed with subsequent correction of clinical parameters. High clinical suspicion and early recognition of this infrequent but important presentation allowed a good outcome in our case.